PEMANFAATAN MIKROKONTROLER AT89S51 DALAM RANCANG BANGUN SISTEM WATER INJECTION BERBASIS MIKROKONTROLER PADA SEPEDA MOTOR - Basori Basori; Subagsono Subagsono; Husin Bugis (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2014)
The rapid development of information technology makes a lot of electronic components used invarious fields. The component that is often used is a microcontroller. The microcontroller is used as theregulator and the automation system. This study aims to design a microcontroller-based water injection (WAI)system on the motorcycle.The experiment was conducted with an experimental method. Object of the research is honda megapro 2009 motorcycle. The design of microcontroller-based WaI done through the following steps: (1) designinga microcontroller-based WaI system using the proximity sensor signals, (2) designing the voltage regulatorcircuit, (3) designing AT89S51 microcontroller circuit, (4) designing injector circuit, (5) designing a series of7-segment display, and (6) making programming the microcontrol ler on the WaI that is used to inject water or amixture of water and methanol into the fuel chamber.The research showed that the microcontroller-based WaI can work correctly when applied tomotorcycles. This system works for injecting water or a mixture of water and methanol into the combustionchamber. Injection is done when the suction valve is open. This condition is known by placing a proximitysensor. On the other hand, the frequency of water or a mixture of water and methanol injection were governedby the microcontroller through the injector.The results showed that the microcontroller-based WaI can work correctly and properly.